High-fidelity entangling gate for double-quantum-dot spin qubits - John M. Nichol (Nature Portfolio, 2017)
Quantum computing: high-fidelity two-qubit entangling gate Scientists have invented a new way to entangle electron spins. Entanglement, or “spooky action at a distance,” is one of the key requirements for a universal quantum computer, because it enables the transfer of information between quantum bits, or qubits. For qubits consisting of electron spins trapped in semiconductors, the Coulomb interaction between electrons can be harnessed to create entanglement. In this approach, however, the coherence of the individual spins is susceptible to spurious charge noise in the semiconductor. Amir Yacoby and colleagues at Harvard University and Purdue University overcame this challenge by using a large magnetic field gradient in a double-quantum-dot spin qubit to suppress the effects charge noise. By mitigating charge-noise-induced decoherence, the team demonstrated a two-qubit entangling gate fidelity of 90%. This high-fidelity entangling operation marks a significant milestone for spin qubits and points the way toward a scalable high-fidelity spin-based quantum computer.